2021
DOI: 10.3168/jds.2020-18676
|View full text |Cite
|
Sign up to set email alerts
|

Effects of herd fertility on the economics of sexed semen in a high-producing, pasture-based dairy production system

Abstract: This study used a stochastic simulation model to estimate the potential economic benefit of using sexed semen in heifers only and in heifers and lactating cows in a high-producing, pasture-based system under 3 fertility scenarios. Three breeding strategies were modeled:(1) only heifers inseminated with sexed semen and cows inseminated with conventional unsexed semen (SSH);(2) both heifers and cows inseminated with sexed semen (SSHC); and (3) a reference scenario in which all females were inseminated with conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 40 publications
1
9
2
Order By: Relevance
“…For TSEX-H and TSEX-HC, the relative P/AI of SS compared with conventional AI was the most critical parameter to the range in annual ∆PROF. Similar to Walsh et al (2021) this parameter was associated with substantially greater financial variability when used in heifers and cows compared with heifers only (see Figure 3). The P/AI of SS relative to conventional AI had more effect on the annual ∆PROF per cow in TSEX-HC (€100.28) than in TSEX-H (€14.23) with more SS doses being used in the TSEX-HC scenario.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…For TSEX-H and TSEX-HC, the relative P/AI of SS compared with conventional AI was the most critical parameter to the range in annual ∆PROF. Similar to Walsh et al (2021) this parameter was associated with substantially greater financial variability when used in heifers and cows compared with heifers only (see Figure 3). The P/AI of SS relative to conventional AI had more effect on the annual ∆PROF per cow in TSEX-HC (€100.28) than in TSEX-H (€14.23) with more SS doses being used in the TSEX-HC scenario.…”
Section: Discussionmentioning
confidence: 77%
“…The difference in our results compared with Calsamiglia et al ( 2018) and Tenhagen et al (2004) may be attributable to the greater economic importance of fertility in seasonal pasture-based systems. Conversely, with the adoption of SS, Walsh et al (2021) and Seidel (2003) found dairy herds with already low reproductive performance using CONV are less likely to realize a financial advantage from sexed semen use as potentially reduced P/AI amplify existing fertility challenges. In less fertile herds adoption of TAI alone may return a positive annual ∆PROF by increasing the proportion of cows bred earlier in the breeding period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations